Morphological characteristics and proportion of leaf blade tissues of elephant grass clones under sheep grazing - Viana, Bruno Leal; Mello, Alexandre Carneiro Leão de; Guim, Adriana; Lira, Mário de Andrade; Dubeux Júnior, José Carlos Batista; Santos, Mércia Virgínia Ferreira dos; Cunha, Márcio Vieira da (Pesquisa Agropecuaria Brasileira, 2018)
The objective of this work was to characterize morphologically elephant grass (Pennisetum purpureum) genotypes and to estimate their proportions of leaf blade tissues under grazing. Two tall varieties (Elephant B and IRI-381) and three short ones (Mott, Taiwan A-146 2.37, and Taiwan A-146 2.114) were evaluated under intermittent sheep grazing as to the following morphological characteristics: plant height, internode length, and leaf blade/culm ratio. Moreover, the proportions of the following leaf blade tissues were estimated: sclerenchyma, adaxial and abaxial epidermis, bulliform cells, vascular bundles, phloem, vascular sheath, xylem, and mesophyll. The short varieties were 28.6% shorter than the tall ones and showed higher leaf blade/culm ratio; Mott and Taiwan A-146 2.114 had the shortest internodes of 3.9 and 4.7 cm, respectively, over ten grazing cycles. The clones differed regarding their proportions of leaf blade tissues, except for abaxial epidermis, phloem, and xylem. The differences in morphological characteristics indicate that the short clones Mott and Taiwan A-146 2.114 are better adapted to sheep grazing, and, therefore, may be recommended for the improvement of pastures.